Immunohistochemical features of fat tissue of epiploon and subcutaneous fat tissue in patients with overweight, obesity and metabolic syndrome. - Militsa, K. M.; Sorokina, I. V.; Myroshnychenko, M. S.; Pliten, O. N. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Fat tissue plays a key role in the development of metabolic syndrome determining the necessity of its complex morphological research. Objective: to identify the immunohistochemical features of fat tissue of epiploon and subcutaneous fat tissue in patients with metabolic syndrome and overweight or obesity of I–III degree. Methods. The material of the study was the autopsy and operational material – fat tissue of epiploon and subcutaneous fat tissue. The authors used histological method for review microscopy and immunohistochemical methods with monoclonal antibodies to the tumor necrosis factor alpha (TNF-α), interleukine-6 (IL-6), insulin and cortisol. Results. It was revealed that in people with a normal body mass index, metabolic syndrome and overweight or obesity in epiploon fat tissue comparing with subcutaneous fat tissue the number of cells expressing receptors for TNF-α, IL-6 and cortisol is significantly greater; in subcutaneous fat tissue the number of cells expressing receptors for insulin is significantly greater. In patients with metabolic syndrome with increased body mass index in subcutaneous fat tissue and epiploon the number of cells expressing receptors for TNF-α and IL-6 is increased, the ability to express adipocyte insulin receptors is reduced while the ability to express receptors to cortisol is increased. Conclusion. Taken together these results evidence the presence of immunohistochemical features of fat tissue of epiploon and subcutaneous fat tissue in patients with metabolic syndrome and overweight or obesity.